How Adult Christians Incorporate Their Faith with the Psychology of Forgiveness: A Qualitative Methods Study - (:unkn) unknown (My University, 2020)
This study examines Christian adult’s perceptions, practices of, and tendencies towards the phenomenon of forgiveness. Research in the field up to this date is valuable in understanding forgiveness theory, efficacy of forgiveness models, as well as the impact of religion and spirituality on forgiveness. However, research has progressed to reduce forgiveness, as well as religion and spirituality to its parts, thus research has moved away from the complete, whole concepts of forgiveness and faith. Lately, research has attempted to fill this gap by understanding how people of faith forgive, though faith groups likely perceive and practice forgiveness differently. Therefore, the purpose of this study is to investigate one faith group’s forgiving. Specifically, it will investigate how Christians define forgiveness, how and why Christians forgive, their experiences of forgiving across time and situations, their development in forgiving, as well as how forgiving is part of Christian identity. A theory of Christian forgiveness, recommendations for practical applications, and implications for further research is provided.
Keywords: Christianity; Forgiveness; Identity; Multiculturalism; Psychology; Qualitative Methods